Identifikasi Potensi dan Tantangan Desa untuk Pengembangan Desa Wisata Luthu Lamweu - Wulandari, Elysa; Yusuf, Myna Agustina; Fakhrana, Siti Zahrina; Hanifah, Winda (Universitas Syiah Kuala, 2024)
Luthu Lamweu Village, located in Aceh Besar Regency, has abundant natural resources, including a waterfall tourist attraction and locally processed products such as Janeng flour, asam sunti (starfruit seasoning), and handicrafts made from coconut leaves. Although the tourist attraction is beginning to draw visitors, access to the site and supporting infrastructure remains limited. This community service program aims to further assess the villages potential for developing as a tourist destination by leveraging its natural and human resources. The strategic approach involves conducting observations and facilitating focus group discussions with local residents to gain insights and foster collaborative planning. The observation results indicate that the village holds significant potential by capitalizing on its abundant natural resources, such as transforming its waterfalls into tourist attractions and leveraging local products as key assets. Findings from the focus group discussions echoed this potential but highlighted a major concern: the lack of community participation, which remains a significant issue for village officials. According to the resource persons presentation, 60% community participation is required to establish a successful tourist village. Therefore, the residents of Luthu Lamweu Village currently need a group that can initiate and mobilize community engagement and enthusiasm.